Public administration’s added value to the competitiveness of national economy - Gordana Žurga (Zbornik radova Ekonomskog fakulteta u Rijeci : časopis za ekonomsku teoriju i praksu, 2011)
The paper presents an explorative study in respect to the public administrations’ added value to the competitiveness of national economies in the context of the Lisbon Strategy. The main research goal was to explore role of governments and their administration in sustaining competitiveness of national economy and to discuss it from different perspectives. As the research methodology we combined comparative analysis of two consecutive studies on public administrations’ added value to the Lisbon Strategy goals performed in 2008 and 2010, with analysis of Lisbon Strategy evaluation conducted by the European Commission, and practical illustration on the case of Slovenia in the context of the Lisbon Strategy and the Europe 2020. Three main components of the hypothesis: (1) need for incorporation of the public administration modernisation and development into developmental goals of the state, (2) monitoring and adjusting the implementation, and (3) identification of interconnections and complementarities for better use of resources were explored and verified in the contexts of Lisbon Strategy adding value to the national competitiveness. Within the research, the hypothesis was proved, as well as the relevance of all three components, especially in the circumstances of the global economic crisis. The main contribution of this paper is explorative description of how governments may, through their public administrations and by implementing and integrating their various roles and activities, add value to competitiveness of their national economies. In the paper some institutional implications are presented, as well as possible areas for further investigation and research.